The effect of injection angle on the suction side of a turbine blade in film cooling system - 177619 Mohd. Nor Musa; Rosli Abu Bakar; Aminudin Abu; Kongres Sains dan Teknologi Malaysia (1994 : Kuala Lumpur)
20